Management Entrenchment, Firm Characteristics and Earnings Management Of Conglomerate Companies In Nigeria - Temitope Olamide Fagbemi; Olubunmi Florence Osemene; Oyinlade Agbaje (Universitas Diponegoro, 2020)
Sometimes the rivalry between shareholders and management is an indication of the level of entrenchment within the corporate environment. Managers are believed to routinely manipulate earnings in order to mislead shareholders about their company's actual economic outlook or performance. As a result, the study investigated the impact of managerial entrenchment, firm characteristics and earnings management of conglomerate companies in Nigeria. Employing the ex-post facto research design, the data was gathered from secondary source of the 6 listed conglomerate companies for the 11-year period running (2008-2018). The study used discretionary accruals a proxy for earnings management and to calculate discretionary accruals, the study used modified Jones model. The result showed that management entrenchment and firm characteristics have Impact on multinational firms ' earnings management in Nigeria. Specifically, from the conglomerate’s entrenchment proxies, CEO’s tenure has a positive and significant impact on earnings management (coff. =1.062821, p-value =0.0367) and management entrenchment as measured by CEO’s shareholding has a negative and insignificant effect on earnings management (coff. =-6252391, p-value = 0.4090) while firm size, profitability and leverage indicated a significant and positive impact on earnings management (coff, = 0.124587, p-value = 0.0000; coff. = 0.006647, p-value = 0.0431 and coff. = 0.032065, p-value = 0.0000). The study therefore recommended among others that management should reduce the debt in their capital structure in order to improve their companies’ value and their capital structure should be majorly financed by equity rather than debt and reduce CEOs tenure to minimise earnings management practices.